Respuesta :
Answer:
Step-by-step explanation:
-4 11/15 because $=-\left(1\frac{2}{5}+2\frac{4}{3}\right)$=−(1
2
5 +2
4
3 )
Show Steps
$\mathrm{Add\:whole\:numbers}\:1+2:\quad3$Add whole numbers 1+2: 3
Show Steps
$\mathrm{Combine\:fractions}\:\frac{2}{5}+\frac{4}{3}:\quad\frac{26}{15}$Combine fractions
2
5 +
4
3 :
26
15
$=-\left(3+\frac{26}{15}\right)$=−(3+
26
15 )
Show Steps
$\mathrm{Convert\:improper\:fractions\:to\:mixed\:numbers}:\quad\frac{26}{15}=1\frac{11}{15}$Convert improper fractions to mixed numbers:
26
15 =1
11
15
$=-\left(3+1\frac{11}{15}\right)$=−(3+1
11
15 )
$\mathrm{Add\:the\:numbers:}\:3+1=4$Add the numbers: 3+1=4
$=-4\frac{11}{15}$